Penyuluhan dan Pelatihan Program Pembinaan Mahasiswa Wirausaha: Membangun Kemitraan Bisnis melalui Media Sosial untuk Pengusaha Muda - Tyoso , Jaluanto Sunu Punjul; Wahyu Handayani, Dyah Ilminingtyas; Hetyorini, Hetyorini (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
Community Service on the theme of building business partnerships through social media aims to increase the knowledge of students who take part in the entrepreneurial student development program (P2MW). P2MW activities get Belmawa funds, Director General of Higher Education to support the entrepreneurial spirit of students, so that after graduating as a scholar, the business can continue. This service method is through counseling and training, namely practicing the material provided in the form of landing pages and promotions. The results of this activity were stated to be very interesting and useful for the participants, as the results of a survey conducted after they underwent training. Future training is expected on finance and marketing.